The Effect of Deferred Tax Assets and Sales Growth on Earnings Management in Manufacturing Companies in the Transportation Sector Listed on the Indonesia Stock Exchange in 2022-2024 - Lulu Lufiah; Daryanto, Daryanto (Managing: Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of deferred tax assets and sales growth on earnings management practices in transportation sector manufacturing companies listed on the Indonesia Stock Exchange in 2022-2024. The research method used was quantitative with a multiple linear regression approach using secondary data from the financial statements of the sample companies. The results of the regression analysis indicate that deferred tax assets have a regression coefficient of 1.105 with a significance value of 0.256 (p > 0.05), thus their effect is partially insignificant on earnings management. Conversely, sales growth has a significant effect with a regression coefficient of 0.135 and a significance value of 0.045 (p < 0.05). Simultaneously, both variables significantly influenced earnings management, with an F-value of 4.170 (p = 0.044) and a coefficient of determination (R²) of 0.510. This means the independent variables explained 51% of the variation in earnings management. This finding suggests that sales growth is a significant factor in earnings management practices in the transportation sector, while deferred tax assets showed no significant effect. This study recommends increasing financial reporting transparency and adding other variables for further research.